Indigenous demosponge spicules in a Late Devonian stromatoporoid basal skeleton from the Frasnian of Belgium. (20th February 2014) - Da Silva, Anne‐Christine; Kershaw, Stephen; Boulvain, Frédéric; Hubert, Benoit L. M.; Mistiaen, Bruno; Reynolds, Alan; Reitner, Joachim
<x xml:space="preserve">Abstract</x> This paper records the first example of a demosponge spicule framework in a single specimen of a Devonian stromatoporoid from the Frasnian of southern Belgium. The small sample (2.5 × 2 cm) is a component in a brecciated carbonate from a carbonate mound in La Boverie Quarry 30 km east of Dinant. Because of the small size of the sample, generic identification is not confirmed, but the stromatoporoid basal skeleton is similar to the genus Stromatopora. The spicules are arranged in the calcified skeleton, but not in the gallery space, and are recrystallized as multi‐crystalline calcite. The spicules fall into two size ranges: 10–20 μm diameter and 500–2000 μm long for the large ones and between 5–15 μm diameter and 50–100 μm length for the small ones. In tangential section, the spicules are circular, they have a simple structure, and no axial canal has been preserved. The large spicules are always monaxons, straight or slightly curved styles or strongyles. The spicules most closely resemble halichondrid/axinellid demosponge spicules and are important rare evidence of the existence of spicules in Palaeozoic stromatoporoids, reinforcing the interpretation that stromatoporoids were sponges. The basal skeleton may have had an aragonitic spherulitic mineralogy. Furthermore, the spicules indicate that this stromatoporoid sample is a demosponge.